2019
DOI: 10.1101/822734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient Receptor Potential Ankyrin 1 Mediates Afferent Signals in the Inflammatory Reflex

Abstract: Survival of an organism requires mechanisms to sense damaging factors in the environment. In mammals, bacterial toxins and inflammatory mediators stimulate nociceptive sensory neurons to activate protective reflexes. Whereas the vagus nerve reflex circuit that protects against damaging inflammation, termed the "inflammatory reflex," was described more than twenty years ago 1,2 , how the vagus nerve detects inflammation to initiate the inflammatory reflex has remained unknown. Here we show that transient recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Cinnamaldehyde can also attenuate apoptosis and promote neuronal survival in DRGs due to oxidative stress, by inhibiting NFkB and decreasing ROS (232). Furthermore, direct activation of TRPA1 on the cervical vagus nerve by the optopharmacological molecule optovin reduces systemic inflammation induced by LPS by significantly decreasing serum TNF (125). Interestingly, LPS itself has recently been found to directly activate TRPA1 directly on sensory neurons, inducing a calcium influx, along with vasodilation, pain, and the release of CGRP in a TRPA1 dependent manner (73).…”
Section: Trpa1mentioning
confidence: 99%
“…Cinnamaldehyde can also attenuate apoptosis and promote neuronal survival in DRGs due to oxidative stress, by inhibiting NFkB and decreasing ROS (232). Furthermore, direct activation of TRPA1 on the cervical vagus nerve by the optopharmacological molecule optovin reduces systemic inflammation induced by LPS by significantly decreasing serum TNF (125). Interestingly, LPS itself has recently been found to directly activate TRPA1 directly on sensory neurons, inducing a calcium influx, along with vasodilation, pain, and the release of CGRP in a TRPA1 dependent manner (73).…”
Section: Trpa1mentioning
confidence: 99%
“…29,31 For fibronectin immunostaining in glomerular explants, we used an efficient sieving method previously described by Rush et al (2018). 32 The protocol initially reported for the isolation of rat glomeruli was modified for mice using a smaller size sieve (40 µm) to collect the glomeruli at the last sieving step. The glomeruli were cultured on sterilized glass coverslips for 96 hours before treatment, after which the glomeruli were fixed with 4% formaldehyde for ~15 minutes, permeabilized with 0.5% Triton X-100 for ~15 minutes, blocked with 2% bovine serum albumin for ~1 hour at room temperature and stained overnight with mouse fibronectin antibody at 4°C.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…However, studies have shown that neuronal and nonneuronal transient receptor potential ankyrin 1 (TRPA1), a cation channel, may be involved in the biological activities of IL‐1. TRPA1 and IL1R1 co‐express in mouse nodose sensory neurons and mediate IL‐1β‐induced vagus nerve activity, thermoregulation, and inflammation 22 . Inhibition of TRPA1 channels attenuated IL‐1β production in primary bronchial epithelial cells and reduced cardiac IL‐1β expression level in doxorubicin‐treated mice 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation